Correction: How FAIR Is Bioarchaeological Data: With a Particular Emphasis on Making Archaeological Science Data Reusable - Alphaeus Lien-Talks (Journal of Computer Applications in Archaeology)
This article details a correction to: Lien-Talks, A. 2024. How FAIR Is Bioarchaeological Data: With a Particular Emphasis on Making Archaeological Science Data Reusable. Journal of Computer Applications in Archaeology, 7(1): 246–261. DOI: https://doi.org/10.5334/jcaa.154